Unconjugated bilirubin differentially affects the redox status of neuronal and astroglial cells - Brito, Maria A. (2015)
We investigated whether nerve cell damage by unconjugated bilirubin (UCB) is mediated by oxidative stress and ascertained the neuronal and astroglial susceptibility to injury. Several oxidative stress biomarkers and cell death were determined following in